The Development of Student Arena Universitas Sumatera with Green Architecture - Sri Wahyuni Hutabarat; Nelson Manumpak Siahaan (International Journal of Architecture and Urbanism, 2022)
With a total number of 32,000 people, it is the reason to develop a student arena building that is more appropriate and sufficient to accommodate all students from 15 faculties. The location chosen was Medan Baru District is the Center for Education and Activities Trade / Business with a land area of 1.5 Ha. Design using a green architectural theme approach is such a way that the building can still maintain the image of the campus, which is a green campus while minimizing adverse impacts on the environment, which is still very natural. This building has supporting buildings that can support student activities from all faculties.